2017
DOI: 10.1177/1359105316685899
|View full text |Cite
|
Sign up to set email alerts
|

Museum object handling: A health-promoting community-based activity for dementia care

Abstract: In a quasi-experimental design (N = 80), this study examined the wellbeing impact of handling museum artefacts, by testing for differences across domain, time, gender and stages of dementia. Results indicated people with early and moderate impairment showed positive increases in wellbeing, regardless of the type of dementia but those with early stage dementia showed larger positive increases in wellbeing. We can feel confident that for most people with early to middle stage dementia, handling museum objects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 23 publications
4
69
0
Order By: Relevance
“…A further division within the field is how the effects of arts-based practices should be understood, with some researchers favouring objective measurement using standardised scales (e.g. Gross et al, 2015;Camic et al, 2017) while others privilege more qualitative approaches to access the subjective experience of engagement with the arts (e.g. Aadlandsvik, 2008;Petrescu et al, 2014).…”
Section: Researching Arts-based Interventions For People With Dementiamentioning
confidence: 99%
See 3 more Smart Citations
“…A further division within the field is how the effects of arts-based practices should be understood, with some researchers favouring objective measurement using standardised scales (e.g. Gross et al, 2015;Camic et al, 2017) while others privilege more qualitative approaches to access the subjective experience of engagement with the arts (e.g. Aadlandsvik, 2008;Petrescu et al, 2014).…”
Section: Researching Arts-based Interventions For People With Dementiamentioning
confidence: 99%
“…This is, perhaps, partially driven by ambitions to evidence the effectiveness of specialised visual arts dementia programmes, such as Memories in the Making © , Opening Minds through Art and TimeSlips © , a storytelling activity (Kinney & Rentz, 2005;Phillips et al, 2010;Gross et al, 2015;Sauer et al, 2016). In particular, researchers favouring concepts such as quality of life (Lawton, 1997) and subjective well-being tend to employ scales such as the researcher-completed Greater Cincinnati Chapter Well-Being Observation Tool (Kinney & Rentz, 2005;Gross et al, 2015;Sauer et al, 2016) or the participant-completed Canterbury Well-being Scale (Johnson et al, 2015;Camic et al, 2017).…”
Section: Researching Arts-based Interventions For People With Dementiamentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that museum activities, including museum visits and object handling sessions, are another example of a potential meaningful activity for people with dementia and their carers. Recent studies reported positive wellbeing impact for people with mild-tomoderate dementia taking part in creative museum activities with their carers, including museum object handling and art viewing in a gallery 7,8 . A further study defined the environmental attributes of the art gallery and their positive emotional and relational effects for people with dementia and their carers 6 .…”
Section: Engagement In People With Dementiamentioning
confidence: 99%